Electrobiochemical skills of Pseudomonas aeruginosa species that produce pyocyanin or pyoverdine for glycerol oxidation in a microbial fuel cell - Zani, Ana Clara Bonizol; Almeida, Érica Janaina Rodrigues de; Furlan, João Pedro Rueda; Pedrino, Matheus; Guazzaroni, María-Eugenia; Stehling, Eliana Guedes; Andrade, Adalgisa Rodrigues de [UNESP]; Reginatto, Valeria (Elsevier, 2023)
Pseudomonas aeruginosa can produce pigments, which mediate external electron transfer (EET). Depending on the mediator, this species can be explored in bioelectrosystems to harvest energy or to obtain chemicals from residual organic compounds. This study has compared the performance of microbial fuel cells (MFCs) inoculated with a Pseudomonas aeruginosa isolate, namely EW603 or EW819, which produce pyocyanin and pyoverdine, respectively. The efficiency of these MFCs in glycerol, a typical residue of biodiesel production, were also compared. The MFCs exhibited different performances. The maximum voltage was 411 and 281 mV m2, the power density was 40.1 and 21.3 mW m−2, and the coulombic efficiency was 5.16 and 1.49% for MFC-EW603 and MFC-EW819, respectively. MFC-EW603 and MFC-EW819 achieved maximum current at 560 and 2200 Ω, at 141.2 and 91.3 mA m−2, respectively. When the system was operated at the respective maximum current output, MFC-EW603 consumed the total glycerol content (11 mmol L−1), and no products could be detected after 50 h. In turn, acetic and butyric acids were detected at the end of MFC-EW819 operation (75 h). The results suggested that P. aeruginosa metabolism can be steered in the MFC to generate current or microbial products depending on the pigment-producing strain and the conditions applied to the system, such as the external resistance. In addition, gene cluster pathways related to phenazine production (phzA and phzB) and other electrogenic-related genes (mexGHI-opmB) were identified in the strain genomes, supporting the findings. These results open new possibilities for using glycerol in bioelectrochemical systems.
Keywords: Acetic acid; Anodic oxidation; Biodiesel; Butyric acid; External resistance; Glycerol